2017
DOI: 10.1108/ejm-04-2015-0213
|View full text |Cite
|
Sign up to set email alerts
|

Self-persuasion as marketing technique: the role of consumers’ involvement

Abstract: Purpose -This paper aims to demonstrate that self-persuasion can be used as a marketing technique to increase consumers' generosity and that the efficacy of this approach is dependent on consumers' involvement with target behavior.Design/methodology/approach -An experimental field-study was conducted to investigate the effects of self-persuasion versus direct persuasion attempts versus no persuasion attempts on consumers' tipping behavior in a lunchroom. Additionally, in a lab experiment, the moderating role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 61 publications
0
32
0
Order By: Relevance
“…Although it is known that how people construe the self could influence self-related cognitive activities, its influence on the effectiveness of self-persuasion is yet to be examined. To the best of our knowledge, self-persuasion studies have until now been exclusively conducted in Western countries (e.g., Baldwin, Rothman, van der Weg, & Christensen, 2013;Bernritter, van Ooijen, & Müller, 2017;Shaw et al, 2015), where people on average hold the independent self-construal (e.g., Cross, et al, 2011;Gudykunst et al, 1996). With regard to smoking, it has been found that question-formulated warning labels successfully increased smoking risk perception and decreased short-term smoking behavior among German and Dutch smokers (Glock, et al, 2013;Müller et al, 2016).…”
Section: Self-persuasion and Self-construalmentioning
confidence: 99%
“…Although it is known that how people construe the self could influence self-related cognitive activities, its influence on the effectiveness of self-persuasion is yet to be examined. To the best of our knowledge, self-persuasion studies have until now been exclusively conducted in Western countries (e.g., Baldwin, Rothman, van der Weg, & Christensen, 2013;Bernritter, van Ooijen, & Müller, 2017;Shaw et al, 2015), where people on average hold the independent self-construal (e.g., Cross, et al, 2011;Gudykunst et al, 1996). With regard to smoking, it has been found that question-formulated warning labels successfully increased smoking risk perception and decreased short-term smoking behavior among German and Dutch smokers (Glock, et al, 2013;Müller et al, 2016).…”
Section: Self-persuasion and Self-construalmentioning
confidence: 99%
“…Theoretically, it is one of the first studies introducing culture as a potential moderator in (self-)persuasion literature. It extends the limited understanding of the self-persuasion effect, especially in correcting the impression that self-persuasion is a one-size-fits-all persuasive technique, and adds to the emerging literature showing that several boundary conditions are of influence [37,46,59]. Practically, we hope our results could inspire relevant health agencies with strategies of designing persuasive messages in mass media campaigns, not only targeting people with Western cultural backgrounds, but also more collectivist immigrant groups that are oftentimes not reached through conventional health campaigns.…”
Section: Discussionmentioning
confidence: 67%
“…Realistically, it will not reduce consumption even close to what is needed to put a dent in alcohol’s contribution to global disease and mortality. Still it should be noted that positive effects in certain situations are found in a relatively new and growing line of experimentation [1720,26,67]. In these studies self-persuasion has consistently outperformed direct persuasion counterparts and no persuasion controls.…”
Section: Discussionmentioning
confidence: 99%